Tandem mass spectrometry findings at autopsy for detection of metabolic disease in infant deaths: postmortem changes and confounding factors. Issue 11 (6th September 2011) - Pryce, J W; Weber, M A; Heales, S; Malone, M; Sebire, N J
Abstract : Aim: Tandem mass spectrometry (MS/MS) is a recommended investigation for sudden unexpected death in infancy (SUDI), but there are limited data regarding yield and potential influencing factors. This study investigates postmortem acylcarnitine profiles in a large cohort of infant deaths from a single centre, including those with metabolic disease. Methods: Acylcarnitine results obtained by MS/MS from routine blood/bile spot samples during the standard autopsy investigation were identified from infant deaths over a 14-year period. Results were categorised as normal or abnormal according to the clinical report by a specialist paediatric biochemist. Possible interdependent variables were assessed, multiple linear regression models were constructed and residual comparison was undertaken. Results: 397 blood and 268 bile MS/MS results were identified from infant cases, including 255 matched blood–bile pairs. There was significant association between blood acylcarnitine findings and postmortem interval (PMI), body mass index and liver weight. A probable cause of death was identified in 40% of sudden death cases, including 18 (2%) with a definite or highly likely cause of death as underlying metabolic disease; this represented 12 (12%) unexpected deaths in the first week of life and six (<1%) aged 7–365 days. Fatty acid oxidation disorders identified included very long chain acyl-CoA dehydrogenase deficiency, medium chain acyl-CoA dehydrogenase deficiency and carnitine transporter defects. Conclusion: Postmortem blood and bile acylcarnitine profiles are influenced by several variables, and PMI can influence MS/MS acylcarnitine results. Metabolic disease may present as SUDI and may be identified from postmortem samples.